Osteogenic markers are reduced in bone-marrow mesenchymal cells and femoral bone of young spontaneously hypertensive rats - De Barros, Thamine Landim [UNESP]; Brito, Victor Gustavo Balera; Do Amaral, Caril Constante Ferreira [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Campanelli, Ana Paula; Oliveira, Sandra Helena Penha de [UNESP] (Elsevier, 2016)
Aims Spontaneously hypertensive rats (SHR) and normotensive rats (W) has significant changes in bone metabolism. The purpose of this study was to investigate whether, the genetic predisposition, is sufficient to induce changes in the osteoblast differentiation and osteogenic markers in the BMSCs or in the femoral bone. For this we use young SHR rats without hypertension, but, with genetic predisposition in compared with young W. Main methods BMSCs were cultured in a proliferation medium (MEM) or osteogenic medium. Osteogenic differentiation was analyzed by proliferation, total protein, alkaline phosphatase, mineralization, and the mRNA expression of RUNX-2, β-cathenin, osterix, bone morphogenetic protein-2 (BMP-2), osteocalcin (OCN), bone sialoprotein (BSP), collagen type I (Col I), and osteopontin (OPN). Key findings Osteoblast differentiation in SHR BMSCs (SHRC) had an increased proliferation compared with W BMSCs (WC). After osteogenic induction, there was greater reduction in proliferation in SHR (SHROM) than in W, in the same condition (WOM). On day 7, although no significant difference in the ALP activity was observed between SHROM and WOM, poor mineralization and osteoblast differentiation was noted in SHROM. The Osterix and β-catenin are involved in the reduced osteoblast differentiation in SHROM. The decreased expression of osteoblast-associated proteins such as OCN, BSP, COL I and OPN revealed poor quality of extracellular matrix (ECM) in SHROM. In the femoral bone, the immunostaining of COL1, BALP, OPN and OCN in SHR was decreased compared with the W. TRAP-positive immunoreactions were observed in major extension in the SHR femur. Significance This study is the first to compare osteoblast differentiation in vitro and femoral bone from SHR and W rats. Our results demonstrated that young SHR (4 weeks old), without hypertension, but with genetic predisposition, had alterations in osteoblast differentiation of BMSCs and in the femoral bone when compared with their progenitor strain, W.
Keywords: Bone markers expression; Femur; Mesenchymal stem cells; Osteogenic differentiation; Spontaneously hypertensive rats (SHR)